ANALISIS SOSIAL DAN EKONOMI MASYARAKAT DALAM PENERAPAN POLA AGROFORESTRI PADA HUTAN KEMASYARAKATAN (STUDI KASUS DESA TEBING SIRING, KABUPATEN TANAH LAUT) - Prayogo Prayogo; Hamdani Fauzi; Dina Naemah (Universitas Lambung Mangkurat, 2020)
Tebing Siring Village is one of the villages that manages community-based forests with an agroforestry system. Socio-economic considerations of an agroforestry system are an important factor in the adoption of the system. The purpose of this study was to describe and analyze the social and economic aspects of the community management pattern of agroforestry in community forests in Tebing Siring Village, Bajuin District, Tanah Laut Regency. The sample determination uses the Slovin formula (Soewadji 2012). The pattern of agroforestry management in Tebing Siring Village uses an Apiculture pattern that combines rubber plants interspersed with kaliandra and kapok randu, the Agrosilvapastura pattern that combines rubber plants with jengkol, cempedak, rice, candlenut, oranges, coconuts, gamal, elephant grass and cattle raising, Agrisilvikultur pattern that combines rubber plants with coffee, gamal, mountain rice and durian, Silvofisheri pattern that combines rubber plants with gamal and fish farming. Socially the community of Tebing Siring Village is 40 respondents, the community likes the agroforestry crop pattern, but the initial results still do not provide the overall benefits of the respondents. The total income of agroforestry originating from Mountain Rice Production is as much as Rp. 6,900,000 with an average of Rp. 627,272 with a contribution reaching 673.85% with an average of 61.26%.Keywords: Tebing Siring Villag; Social and economic aspects; Agroforestry